TEMPORAL AND SPATIAL ANALYSIS OF IONOSPHERIC SCINTILLATION DISTRIBUTION IN INDONESIAN SECTOR - ABADI (NIM: 20211026); Pembimbing : Wahyu Srigutomo, Ph.D, PRAYITNO
We have analyzed low-latitude ionospheric scintillation in Indonesia using two GPS receivers installed at Bandung (107.6°E, 6.9°S; magnetic latitude 17.5°S) and Pontianak (109.3°E, 0.02°S; magnetic latitude 8.9°S). This study is aimed to characterize climatological and directional ionospheric scintillation occurrences. We used amplitude scintillation (S4 index) data obtained from the instruments from 2009 until 2011. We summarized mainly our results: (1) ionospheric scintillation occurrences in post-sunset period (1800–0100 LT) during equinox months (plasma bubble season) at two sites can be ascribed to be due to plasma bubble; (2) We found asymmetry equinoctial of ionospheric scintillation occurrence in 2010, that is the occurrence in March 2010 is significantly higher than in October 2010; (3) By using directional analysis of two sites, we found distribution of scintillation occurrences is generally concentrated between two sites that indicating average location of EIA (equatorial ionization anomaly) crest; (4) remarkable finding is scintillation occurrences distribution for two sites in field-aligned directions affected by field-aligned plasma irregularities is to be first reported by observation in low-latitude region; (5) in general, ionospheric scintillation occurrence in Bandung is more higher than in Pontianak; and (6) distribution of scintillation occurrences at Pontianak is concentrated at southwest direction that is very likely to be associated with plasma bubble tilts west with the increasing latitude.